Earthquake of July 1980 in Far Western Nepal (Journal of Nepal Geological Society, 1982)
This paper is an attempt to study the seismicity of the Nepal Himalaya and the earth-quake of July 1980 of Magnitude 6.5 in western Nepal on its regional geological framework. A new fault plane solution is obtained for this earthquake from the study of P wave motion on WWSSN Seismograms at 34 stations. The solution given by Kanamori and Given is not in conformity with the observed P wave first motion. The damaged area is elongated in the azimuth of 110°-120°, which is parallel to the strike of the nodal plane obtained in this study. From the study of the seismicity of Nepal region it is observed that most of the seismicity in recent years is confined in between the Main Central Thrust and the Main Boundary Thrust.